Electronic structure regulation of CoMoS catalysts by N, P co-doped carbon modification for effective hydrodesulfurization. (15th August 2022) - Zhang, Ge; Yang, Fan; Xu, Zhusong; Che, Sai; Sun, Siyuan; Xu, Chong; Ma, Guang; Yang, Wang; Wei, Qiang; Li, Yongfeng
Highlights: NPC as electronic structure enhancer for Mo led a higher sulfided degree of Mo species. Electron-rich NPC enhance the dispersion of Mo species by electron donating effect. The NPC layer decrease the excessively strong interaction between support and active metal phase. The electron transfer from NPC to MoS2 improve the HDS activity of MoS2 . The electron transfer effect of NPC for MoS2 increase DDS pathway. Abstract: Extensive efforts have been devoting to remove sulfur from transportation fuels to protect the environment. Here we present the synthesis of highly efficient hydrodesulfurization (HDS) catalysts by loading Co/Mo sulfides on various carbon modified γ-Al2 O3 substrates. The synthetic strategy features facile sequential impregnation and pyrolysis process. The morphology, surface property, and pore structure of the catalysts were characterized by various techniques, and the catalytic performance were evaluated by a fixed-bed hydrodesulfurization unit. The optimized CoMo/NPC@γ-Al2 O3 showed superior dibenzothiophene (DBT) removal rates (99%) and kHDS value (5.12 × 10 -7 mol g −1 s −1 ) than those of CoMo@γ-Al2 O3 at a relatively low temperature of 280 °C, revealing the effective modulation of carbon backbone. This remarkable HDS activity originated from the high sulfidation degree as well as electron-rich Mo species, which was attributed to the electron donating effect by N, P co-doping in the carbon skeleton. In addition, after the carbon modification, the decreased acid sites in γ-Al2 O3 support and the electron-rich Mo sulfide resulted in a high selectivity of direct desulphurization (DDS) pathway over hydrogenation (HYD), leading to significant hydrogen energy economy. The density functional theory (DFT) calculations confirmed that the electron-donating effect of NPC enhanced the dispersion of Mo species and weakened the Mo-O/Mo-S bonds, creating more active sites. This work provides an effective strategy for rational design and synthesis of highly-efficient HDS catalysts in practical industrial application.